One‐lung ventilation in a patient with sickle cell disease. Issue 1 (2nd May 2013) - Francis, Katharine; Collins, Jonathan; Pigott, David
Summary: We describe the safe management of a patient with sickle cell disease requiring one‐lung ventilation for video‐assisted thoracoscopic thymectomy. Though this technique is associated with a risk of hypoxaemia and, therefore, sickle crisis, our technique resulted in minimal disruption to haemoglobin oxygen saturations and no immediate rise in the sickle haemoglobin fraction. We have found no previous reports of the management of sickle cell disease patients presenting for surgery requiring one‐lung ventilation.